Incidence and inhospital outcomes of coronavirus disease 2019-associated pulmonary aspergillosis in the United States - Aditya Sharma; Aditi Sharma; Ayman O Soubani (Annals of Thoracic Medicine, 2024)
OBJECTIVE: The aim of this study was to estimate the predictors, associations, and outcomes of COVID-19-associated pulmonary disease (CAPA) in the United States. STUDY DESIGN AND METHODS: This retrospective cohort study was performed by using the National Inpatient Sample Database 2020 to identify coronavirus disease 2019 (COVID-19) and CAPA hospitalizations. Baseline variables and outcomes were compared between COVID-19 hospitalizations without aspergillosis and those with aspergillosis. These variables were then used to perform an adjusted analysis for obtaining predictors and factors associated with CAPA and its inhospital mortality. RESULTS: Of the 1,020,880 hospitalizations identified with the principal diagnosis of COVID-19, CAPA was identified in 1510 (0.1%) hospitalizations. The CAPA cohort consisted of a higher proportion of males (58%) as well as racial and ethnic minorities (Hispanics, Blacks, and others [including Asian or Pacific islanders, native Americans]). Inhospital mortality was significantly higher (47.35% vs. 10.87%, P < 0.001), the average length of stay was longer (27.61 vs. 7.29 days, P < 0.001), and the mean cost per hospitalization was higher ($121,560 vs. $18,423, P < 0.001) in the CAPA group compared to COVID-19 without aspergillosis. History of solid organ transplant, chronic obstructive pulmonary disease, and venous thromboembolism were associated with higher odds of CAPA among other factors. The use of invasive mechanical ventilation (adjusted odds ratio [aOR] 6.24, P < 0.001), acute kidney injury (aOR 2.02, P = 0.028), and septic shock (aOR 2.07, P = 0.018) were associated with higher inhospital mortality in the CAPA cohort. CONCLUSION: While CAPA is an infrequent complication during hospitalizations for COVID-19, it significantly increases all-cause mortality, prolongs hospital stays, and leads to higher hospital expenses compared to COVID-19 cases without aspergillosis.